Perancangan Sistem Monitoring Pelanggaran Siswa Berbasis Android di SMKN 4 Kota Serang - Yoga Dwi Septiyanto; Bagus Dwicahyono; Siswo Wardoyo (CV. ALIM'SPUBLISHING, 2026)
This study aims to develop and evaluate an Android-based application for monitoring student violations at SMK Negeri 4 Kota Serang, which previously relied on a manual, ledger-based recording system that was slow, error-prone, and difficult to track; interviews at the school found that more than 60% of 1,414 registered students had been recorded for a violation over three years. Using the Research and Development (R&D) method with a Waterfall model, the system was built with Kodular and Firebase Realtime Database and evaluated through black-box testing, media-expert validation, and user (counselor) response testing. The application provides administrator and teacher roles with features for managing student, teacher, and class data, recording violations, generating class recaps, visualizing violation charts, and ranking violators. Black-box testing showed that all tested functions (100%) worked as expected, expert validation produced an average score of 4.36 (